Effects of storage temperature on the quality of eggs coated by cassava starch blended with carboxymethyl cellulose and paraffin wax - Pornchai Rachtanapun (Elsevier, 2022)
ABSTRACT: A blend of cassava starch (CS), carboxymethyl cellulose (CMC), and paraffin was prepared as a coating material to maintain the quality of eggs during 4 wk of storage at different temperatures. The efficacy of the CS/CMC/paraffin (6/1/0.5% w/v) coating was investigated in terms of the Haugh unit (HU), weight loss, pH, and microbial load at the end of storage. The best egg storage temperature was 4°C, which maintained an HU of grade AA in coated and uncoated eggs for 4 wk. Lower weight loss (2.14%) was observed in coated eggs at 4°C storage than at 30°C storage (3.26%). The pH in the albumen of coated and uncoated eggs at 4°C increased from 6.84 to 6.88 and 7.01 to 7.03, respectively, after 4 wk of storage. No microbes were detected in the coated and uncoated eggs at 4°C. The maximum microbial count was 728 ± 35 cfu/mL in uncoated eggs at 30°C storage. Egg coating prevented microbial contamination of eggs stored at 30°C for 4 wk. The freshness of the eggs did not affect the nutrient content. The egg-coating material effectively maintained egg quality, prevented microbial contamination of eggs, and increased the shelf life of eggs at storage temperatures of 25 and 30°C.